Propriedades térnicas de géis e xerogéis híbridos de sílica/orgânico à base de GPTS-TEOS com diferentes concentrações de GPTS - Ramponi, Tereza Cristina [UNESP] (2013)
In the present work the thermal characteristics of gels and xerogels of Silica/organic hybrids derived from different concentrations of GPTS-TEOS were investigated by thermal analysis (TG, DTA, and DSC). The preparation of gels of the Silica/organic hybrid matrix was held through the sol-gel process, consisting by the hydrolysis of alkoxides GPTS and TEOS in proportion (1:1) and (1:2) that was promoted in acidic conditions under reflux and stirring at 80oC/2h, producing the matrix in the colloidal state (sol). Gels were prepared by addition of NH4OH to the sol, promoting gelation of sol in sealed plastics containers. Part of the gels samples was analyzed by TG, DTS and DSC techniques in order to characterize water loss and degradation of the polymeric “epoxy” groups present in the structure of the silica derived from the GPTS alkoxide. Another set of samples was dried at 80oC/48h to obtain xerogels (dried gels) and analyzed by the same techniques. We obtained the characteristics temperatures of the matrix by the techniques DTA, DSC and TG, under measurements of thermal analysis until 800oC and 600oC in case of DSC. By thermal analysis (TG, DTA, and DSC) the main endothermic events (loss of water, melting, pyrolysis) and exothermic events (burning of the polymer) of the GPTS-TEOS matrix were determined